A scalable attribute-set-based access control with both sharing and full-fledged delegation of access privileges in cloud computing. (January 2017) - Ahuja, Rohit; Mohanty, Sraban Kumar; Sakurai, Kouichi
Highlights: The Proposed scheme employs Ciphertext-policy Attribute-Set-Based Encryption for secure sharing of data using cloud servers. The proposed scheme provides users complete liberty on delegation of their access privileges. Shared access privileges are provided to group of users for jointly addressing the role. Graphical abstract: Abstract: The benefits of cloud computing motivate enterprises to migrate their IT infrastructure on cloud servers. Enterprise needs to entrust untrusted cloud service provider, which gives rise to various security and privacy concerns. To address these concerns, numerous schemes in cloud computing employed attribute-based encryption schemes. However, existing schemes are neither flexible enough to provide users complete liberty on delegation of their access privileges nor grant shared access privileges among users of a group to jointly address a responsibility. This paper introduces hierarchical attribute-set-based access control scheme by employing ciphertext-policy attribute-set-based encryption with a hierarchical structure of users to achieve scalability. The proposed scheme simultaneously achieves the notion of fine-grained cum flexible access control, privacy preserving, efficient data utilization and imperatively provides users full-fledged liberty on delegation of their access privileges. Furthermore, we formally prove that proposed scheme is secure under decisional bilinear Diffie–Hellman assumption.